Lipoamide Alleviates Oxidized Fish Oil-Induced Host Inflammatory Response and Oxidative Damage in the Oviduct of Laying Hens - Liu, Qingxiu; Li, Wenxiang; Zhang, Jiatu; Zhao, Lihong; Ji, Cheng; Zhang, Jianyun; Huang, Shimeng; Ma, Qiugang (Frontiers in Veterinary Science, 2022)
Fish oil is an important source of lipid in functional food and aquafeeds. However, the harmful effects of oxidized fish oil on host metabolism and reproductive health are not yet clear. Also, lipoamide (LAM) has been widely studied as an agent for alleviating various diseases associated with oxidative disruption. Therefore, in the current study, to investigate the effects of LAM in alleviating oxidized fish oil-induced decline in reproductive performance and oxidative damage to the oviduct in laying hens. We constructed a 1% fresh fish oil (FO) model, a 1% oxidized fish oil (OFO) model and a LAM model with 0.1% oxidized fish oil (OFO + LAM) added at 100 mg/kg to explore the antioxidant effect of LAM. Herein, these results were evaluated by breeding performance, immune responses, estrogen, and antioxidant indices of serum samples, as well as number of follicles and antioxidant parameters of oviducts. From the results, compared with the FO group, OFO significantly decreased the egg laying rate, increased the contents of total protein (TP) and inflammatory factors (TNF-α, IL-6, IL-8, and INF-γ) and reduced the concentrations of anti-oxidation (T-AOC, T-SOD, GSH-Px, GSH, GR, CAT, and HRSA) in serum samples, as well as reduced the levels of anti-oxidation indexes in oviduct tissues (P < 0.05). Of note, the supplementation of LAM could significantly increase the laying performance, improve the levels of serum immunoglobulins (IgA, IgG, and IgM), serum estrogen (P and E2), and serum antioxidant parameters (T-AOC, T-SOD, GSH-Px, GSH, GR, CAT, and HRSA) and decrease the concentrations of serum inflammatory cytokines (TNF-α, IL-6, IL-8, and INF-γ) in laying hens following OFO administration (P < 0.05). In addition, LAM could dramatically increase the contents of antioxidant factors (P < 0.05) in oviducts and enhance the secretion capacity of the uterine part. Taken together, oxidized fish oil caused host metabolic dysfunction, oxidative damage, uterine morphological abnormalities, and alterations of ovarian function. These results suggested that LAM administration could alleviate host metabolic dysfunctions and inflammatory damage, and then ameliorate oxidative damage in the oviduct induced by oxidized fish oil, ultimately improving reproductive function.